Contributions of social participation to the dynamic balance, mobility, and muscle strength of different age groups of older people: a cross-sectional study - Patrícia Azevedo Garcia; Arielle Rodrigues Maringolo; Sabrina Nunes Gabriel; Cristiane de Almeida Nagata; Tânia Cristina Dias da Silva Hamu (Universidade de São Paulo, 2023)
ABSTRACT This study aimed to investigate the contributions of social participation in health promotion groups and regular physical exercise programs to the physical and functional performance of different age groups of community-dwelling older adults. This is a cross-sectional study including 266 older adults. Physical and functional performances (dependent variables) were characterized based on dynamic balance (alternate step test), mobility (timed up and go test), upper (handgrip dynamometer) and lower limbs muscle strength (Sit-to-stand test). Participants were questioned about active social participation in primary care groups and in physical exercise programs. The data were analyzed by linear regressions. Among individuals aged over 80 years, women participated in less health promotion groups and both sexes practiced less physical exercise. Age combined with regular exercise significantly explained 18.7% of dynamic balance and 22.8% of lower limb muscle strength in women. Despite social participation, for men, age alone explained 11.9% of lower limb strength and 11.5% of mobility. Therefore, social participation in physical exercise programs was a protective factor for these physical and functional differences between women's age groups. Among men, mobility and lower limb strength performance reduced with aging, regardless of social participation.